In Situ Porous Structure Characterization of Electrodes for Energy Storage and Conversion by EQCM-D: a Review. (1st April 2017) - Levi, Mikhael D.; Shpigel, Netanel; Sigalov, Sergey; Dargel, Vadim; Daikhin, Leonid; Aurbach, Doron
Abstract: A great advantage of non-gravimetric vs. conventional gravimetric mode of quartz-crystal microbalance (QCM) has been demonstrated for quantification of the hydrodynamic interactions of rigid porous electrode coatings with contacting electrolyte solutions. The complex frequency change of these electrodes measured by multiharmonic EQCM-D (Electrochemical QCM with Dissipation Monitoring) contains implicit information about the initial porous electrode structure at open-circuit potential and its minute changes caused by Li-ions intercalation into the electrode host. Fitting suitable hydrodynamic models to the experimental complex frequency changes allows determination of the initial geometric parameters of the porous electrode in contact with solution as well as their potential-dependent changes. Validation of structural parameters derived by the hydrodynamic models for a large number of porous structure geometries using penetration depth as a unique mesoscopic independent variable should be done using complementary techniques with different resolution power. A meaningful application of EQCM-D in Li-ion batteries R&D is only possible under strict control over numerous contributions to the total complex frequency change from the processes accompanying intercalation of ions into the electrode (viscoelastic effects of binders, formation of surface-electrolyte interface, side reactions with gas evolution, etc.)